Summer mortality of selected juvenile pacific oyster Crassostrea gigas under laboratory conditions and in comparison with field performance - Degremont, Lionel; Soletchnik, Patrick; Boudry, Pierre (Journal of Shellfish Research, 2010)
This study reports mortality under laboratory conditions in unselected controls and two lines of juvenile Pacific oysters Crassostrea gigas, previously selected for their high or low survival in the field during the summer period. Oysters were also deployed in field conditions and mortality between both conditions was then compared. In the laboratory, mortality was observed in all experiments and it always lasted for a week indicating that mortality under laboratory conditions was a short-term event. It was also shown that mortality could be repeated for a batch in several experiments using oysters which never experienced any abnormal mortality. This approach could facilitate further studies to investigate the causes of mortality by allowing repeated trials during a summer. Differences in mortality between the resistant and the susceptible selected lines confirmed the positive response to selection under laboratory conditions. Batches that performed well in the laboratory also showed high survival in the field, and the results of those exhibiting low survival in the laboratory trials were also mirrored in the field. Finally, challenging oysters with heat stress is proposed as a useful method for estimating the survival capacity of hatchery-produced and wild-caught spat used by the oyster industry.